Preparation of CdO Rhombus-like Nanostructure and Its Photocatalytic Degradation of Azo Dyes from Aqueous Solution - Azadeh Tadjarodi; Mina Imani; Hamed Kerdari; Keyvan Bijanzad; Dorsan Khaledi; Maryam Rad (Nanomaterials and Nanotechnology)
In this work, a special rhombus-like structure of CdO composed of particles at the nanometre scale was successfully synthesized for the first time. A facile hydrothermal process with a post-reaction calcination was employed to prepare this nanomaterial. Scanning electron microscopy (SEM) images showed that the obtained rhombus-like structure consists of nanoparticles with an average size of 29 nm. The band gap energy of 1.9 eV based on a diffuse reflectance spectroscopy (DRS) showed that the product can be favourable to photoactivity in the visible region of sunlight. The prepared sample was employed to destruct carcinogenic azo dyes, such as Congo Red (CR), Malachite Green (MG) and Crystal Violet (CV). The obtained results showed that the CdO with the special morphology was able to effectively catalyse the degradation of these pollutants. The related decolourization efficiencies were obtained by up to 100% after various lengths of time of light irradiation. It was concluded that the photodegradation of the mentioned organic dyes under visible light irradiation by a CdO rhombus-like nanostructure follows the first-order reaction kinetics. The effect of the initial pH and contact time on the percentage of the decolourization of these organic dyes was also studied.